Encryption Standards and Tokenization Techniques for Securing Banking Cloud Infrastructure (Cybersecurity and Network Defense Research, 2021)
The growing reliance of the banking sector on cloud infrastructure necessitates robust security frameworks to protect sensitive customer information and comply with regulatory standards. This paper investigates the implementation of encryption standards and tokenization techniques tailored for securing banking cloud infrastructures. Emphasis is placed on advanced encryption methods, their suitability for various banking operations, and their compliance with established standards, including Payment Card Industry Data Security Standards (PCI DSS) and Federal Financial Institutions Examination Council (FFIEC) guidelines. The study evaluates symmetric encryption algorithms such as Advanced Encryption Standard (AES) for data-at-rest and Transport Layer Security (TLS) for data-in-transit, discussing their respective strengths and vulnerabilities in cloud environments. Furthermore, the analysis extends to emerging encryption techniques, including homomorphic encryption and quantum-resistant algorithms, highlighting their potential to address evolving cybersecurity threats.In addition to encryption mechanisms, the paper explores tokenization as a complementary approach to enhance data security by replacing sensitive information with non-sensitive tokens. The effectiveness of tokenization in mitigating risks associated with data breaches, ensuring compliance with industry standards, and supporting secure payment processing is critically analyzed. Different tokenization architectures, including format-preserving and vaultless tokenization, are examined with a focus on their scalability, performance implications, and compatibility with cloud-native applications. Case studies demonstrate the practical application of these techniques in real-world banking scenarios, showcasing their ability to meet stringent security and performance requirements.Regulatory compliance remains a cornerstone of banking security, and this paper delves into the integration of encryption and tokenization techniques with regulatory mandates. The role of key management systems (KMS), secure cryptographic modules, and centralized governance frameworks in maintaining compliance while ensuring operational efficiency is extensively discussed. Special attention is given to the challenges of securing multi-tenant cloud environments, including data segregation, insider threats, and third-party risks.This research highlights the critical interplay between technological innovation and regulatory adherence, emphasizing that robust encryption and tokenization strategies are indispensable for securing modern banking cloud infrastructures. By bridging the gap between theory and practice, this paper aims to guide financial institutions in adopting advanced security measures that align with regulatory requirements and emerging cybersecurity challenges.